Recovery of gut microbiota of healthy adults following antibiotic exposure. (November 2018) - Palleja, Albert; Mikkelsen, Kristian; Forslund, Sofia; Kashani, Alireza; Allin, Kristine; Nielsen, Trine; Hansen, Tue; Liang, Suisha; Feng, Qiang; Zhang, Chenchen; Pyl, Paul; Coelho, Luis; et al.
Abstract To minimize the impact of antibiotics, gut microorganisms harbour and exchange antibiotics resistance genes, collectively called their resistome. Using shotgun sequencing-based metagenomics, we analysed the partial eradication and subsequent regrowth of the gut microbiota in 12 healthy men over a 6-month period following a 4-day intervention with a cocktail of 3 last-resort antibiotics: meropenem, gentamicin and vancomycin. Initial changes included blooms of enterobacteria and other pathobionts, such asEnterococcus faecalis andFusobacterium nucleatum, and the depletion ofBifidobacterium species and butyrate producers. The gut microbiota of the subjects recovered to near-baseline composition within 1.5 months, although 9 common species, which were present in all subjects before the treatment, remained undetectable in most of the subjects after 180 days. Species that harbour β-lactam resistance genes were positively selected for during and after the intervention. Harbouring glycopeptide or aminoglycoside resistance genes increased the odds of de novo colonization, however, the former also decreased the odds of survival. Compositional changes under antibiotic intervention in vivo matched results from in vitro susceptibility tests. Despite a mild yet long-lasting imprint following antibiotics exposure, the gut microbiota of healthy young adults are resilient to a short-term broad-spectrum antibiotics intervention and their antibiotics resistance gene carriage modulates their recovery processes. Here the authors show that the human gut microbiome can recover after a clinically relevant, broad-spectrum antibiotic treatment and characterization of the resistome indicates that antibiotic resistance genes can impact the recovery process.